2018
DOI: 10.1123/pes.2017-0178
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of 3-Month Skill-Based and Plyometric Conditioning on Fitness Parameters in Junior Female Volleyball Players

Abstract: Selected variables can be improved by adding 2 plyometric training sessions throughout the period of 12 weeks. Additional skill-based conditioning did not contribute to improvement in the studied variables compared with regular volleyball training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(63 citation statements)
references
References 41 publications
1
46
0
6
Order By: Relevance
“…Chin thickness correlated largely to very largely with skinfolds in torso with large fat stores (chest II, abdomen, and iliac crest), which might explain the relevance of chin skinfold for performance indices. Skinfold thickness was used widely in female volleyball, where it was shown that the number and anatomical sites of skinfolds varied by study [5,[19][20][21]. Thus, the present study highlighted the importance of evaluating not only the sum of skinfolds, but also the patterns of SAT distribution among skinfolds.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…Chin thickness correlated largely to very largely with skinfolds in torso with large fat stores (chest II, abdomen, and iliac crest), which might explain the relevance of chin skinfold for performance indices. Skinfold thickness was used widely in female volleyball, where it was shown that the number and anatomical sites of skinfolds varied by study [5,[19][20][21]. Thus, the present study highlighted the importance of evaluating not only the sum of skinfolds, but also the patterns of SAT distribution among skinfolds.…”
Section: Discussionmentioning
confidence: 67%
“…The skinfold method was selected to study SAT distribution in order for the findings to have practical relevance considering the widely cost-effective use of this method in field [5,19,20,23]. It was acknowledged that the DEXA method would not be an accurate method for SAT patterning analyses [30].…”
Section: Equipment and Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…The horizontal jump tests included two exercises: The standing long jump and the depth leap long jump. One study included both male and female participants [56], one included only males [58] and another included only females [48]. The study conducted by Milić et al [52] did not report the genre of the participants.…”
Section: Resultsmentioning
confidence: 99%
“…Studies conducted by Milić et al [52] and Çımenlı et al [57] revealed a significant increase in horizontal jump performance after the plyometric training intervention. However, another study did not show significant differences in this regard [56], and the study carried out by Gjinovci et al [48] presented only a small effect of plyometric training on horizontal jump performance.…”
Section: Resultsmentioning
confidence: 99%